2015
DOI: 10.1681/asn.2014050464
|View full text |Cite
|
Sign up to set email alerts
|

Provider Visits and Early Vascular Access Placement in Maintenance Hemodialysis

Abstract: Medicare reimbursement policy encourages frequent provider visits for patients with ESRD undergoing hemodialysis. We hypothesize that patients seen more frequently by their nephrologist or advanced practitioner within the first 90 days of hemodialysis are more likely to undergo surgery to create an arteriovenous (AV) fistula or place an AV graft. We selected 35,959 patients aged $67 years starting hemodialysis in the United States from a national registry. We used multivariable regression to evaluate the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
(47 reference statements)
0
17
0
2
Order By: Relevance
“…The regional variation with respect to time to AVF maturation may reflect known geographic variation in timing of provider visits and first cannulation attempts. 46, 47 However, the geographic heterogeneity with respect to AVF maturation requires further investigation, and may reveal unrecognized practice variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regional variation with respect to time to AVF maturation may reflect known geographic variation in timing of provider visits and first cannulation attempts. 46, 47 However, the geographic heterogeneity with respect to AVF maturation requires further investigation, and may reveal unrecognized practice variations.…”
Section: Discussionmentioning
confidence: 99%
“…7, 34, 51 Vascular access placement reimbursement is significantly lower than other vascular operations, 52 which likely result in lower priority for scarce operating time. Expanded pre-dialysis CKD and early ESRD care, with expanded patient educational efforts addressing vascular access prior to the surgical evaluation, may also be of benefit 7, 47, 53, 54 , particularly as patients may be resistant to access placement, 24, 55 resulting in patient-related factors delaying work-up, surgical evaluation, and scheduling.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we previously found that one additional physician (or advanced practitioner) visit in the period following hospital discharge predicted a 3.5% decrease in the absolute probability of a patient being re-hospitalized within 30 days, 18 while more frequent visits of patients who recently initiated dialysis were associated with an increased likelihood of receiving an arteriovenous fistula or graft. 34 …”
Section: Discussionmentioning
confidence: 99%
“…13 This also raises the possibility that the reimbursement reform did not yield other benefits that have been associated with more physician visits in cross-sectional studies such as improved achievement of clinical performance targets. 34, 36, 37 …”
Section: Discussionmentioning
confidence: 99%
“…Notably, this population is highly vulnerable for complications, including an increased risk for hospital readmissions (29). Even in the ESRD setting, more frequent provider (physician or extender) visits have been associated with improved clinical outcomes (30,31). Importantly, patients are often assessed by physician extenders (physician assistants or nurse practitioners) in ESRD facilities, but most such providers will not have significant experience or training in the care of Establish a distinct payment system for outpatient AKI dialysis care in ESRD facilities Establish reimbursement rates for AKI dialysis care that reflect a higher cost of care than for patients with ESRD because of increased monitoring needs (both physician assessments and laboratory testing) Formal recognition as a separately billed entity will encourage centers to develop AKI-specific protocols and procedures Coverage of outpatient dialysis by Medicare will permit characterization of this high-risk AKI population through significantly greater data capture Prioritize research to improve recovery of renal function Support research on therapeutics to promote recovery of renal function after AKI Support research to develop prediction tools or novel biomarkers for recovery of renal function after AKI requiring dialysis Support research aimed at establishing best practices for the promotion of recovery of renal function in patients with AKI requiring dialysis patients with AKI.…”
Section: Develop Specific Protocols For Patients With Aki-dmentioning
confidence: 99%